MANAJEMEN ZAKAT DI NEGARA MESIR - Ayna Azzahra; Maryam Batubara (Smart Education, 2026)
Abstract: This study aims to provide a comprehensive analysis of the zakat management system in Egypt, focusing on its institutional structure as well as the mechanisms of zakat collection and distribution as an important instrument in Islamic social finance to support social welfare and reduce economic inequality. The research uses a literature study method with a Systematic Literature Review approach, drawing data from scientific journals, academic books, and official documents to ensure a comprehensive and reliable analysis. The results show that zakat in Egypt is voluntary and not mandated by the state, yet its management remains relatively well-organized through formal institutions such as Islamic banks, charitable organizations, and community-based social institutions, creating a balance between accountability and flexibility in its distribution. The potential of zakat in Egypt is quite significant, reaching approximately one percent of the gross domestic product, indicating its strategic role in supporting socio-economic development; however, its utilization has not been fully optimized, particularly in reducing poverty and addressing income inequality. This limitation is influenced by several factors, including weak coordination among institutions, differences in governance standards, and limited integration with national development policies, thus highlighting the need for stronger coordination, improved regulatory frameworks, and enhanced policy support to ensure that zakat can function more effectively and sustainably in promoting socio-economic development in Egypt. Keywords: Zakat, Zakat Management, Egypt, Social Welfare, Poverty, Institutional System. Abstrak: Penelitian ini bertujuan untuk memberikan analisis komprehensif mengenai sistem manajemen zakat di Mesir dengan fokus pada struktur kelembagaan serta mekanisme pengumpulan dan distribusi zakat sebagai instrumen penting dalam keuangan sosial Islam untuk mendukung kesejahteraan masyarakat dan mengurangi ketimpangan ekonomi. Penelitian ini menggunakan metode studi pustaka dengan pendekatan Systematic Literature Review dengan sumber data yang berasal dari jurnal ilmiah, buku akademik, dan dokumen resmi guna memastikan analisis yang komprehensif dan dapat dipercaya. Hasil penelitian menunjukkan bahwa zakat di Mesir bersifat sukarela dan tidak diwajibkan oleh negara, namun pengelolaannya tetap terorganisasi dengan baik melalui lembaga formal seperti bank Islam, organisasi filantropi, dan lembaga sosial berbasis masyarakat sehingga menciptakan keseimbangan antara akuntabilitas dan fleksibilitas dalam penyalurannya. Potensi zakat di Mesir tergolong besar dengan capaian sekitar satu persen dari produk domestik bruto, yang menunjukkan peran strategisnya dalam mendukung pembangunan sosial ekonomi; namun demikian, pemanfaatannya belum sepenuhnya optimal, terutama dalam mengurangi kemiskinan dan mengatasi ketimpangan pendapatan. Keterbatasan ini dipengaruhi oleh beberapa faktor seperti lemahnya koordinasi antar lembaga, perbedaan standar tata kelola, serta rendahnya integrasi dengan kebijakan pembangunan nasional, sehingga diperlukan peningkatan koordinasi, penguatan kerangka regulasi, dan dukungan kebijakan yang lebih optimal agar zakat dapat berfungsi secara lebih efektif dan berkelanjutan dalam mendorong pembangunan sosial ekonomi di Mesir. Kata Kunci: Manajemen Zakat, Kesejahteraan Sosial, Kemiskinan, Sistem Institutional, Zakat